Swarm intelligence 8th International Conference, ANTS 2012, Brussels, Belgium, September 12-14, 2012. proceedings - Dorigo, Marco (Lecture notes in Computer Science, 2012)
This book constitutes the proceedings of the 8th International Conference on Swarm Intelligence, held in Brussels, Belgium, in September 2012. This volume contains 15 full papers, 20 short papers, and 7 extended abstracts carefully selected out of 81 submissions. The papers cover various topics of swarm intelligence.